Substrate, catalyst, and solvent: the triune nature of multitasking reagents in hydroboration and cyanosilylation - Dixit, Ruchi; Bisai, Milan Kumar; Yadav, Sandeep; Yadav, Vinita; Sen, Sakya S.; Vanka, Kumar (Organometallics, 2021)
A truly green chemical process would avoid the use of an external catalyst, while still achieving high efficiency. This has been realized in the very recent past for hydroboration, cyanosilylation, acetalization, and the aza-Michael addition, among other reactions. The current combined computational and experimental study unlocks the secret to how this highly desirable outcome is accomplished: one of the reactants in the process also acts as the catalyst. Specifically, this is shown (i) for the important hydroboration reaction, with pinacolborane (HBpin) as the hydroborating reagent and benzaldehyde, acetophenone, benzoic acid and p-methoxyphenylacetylene as the hydroborated substrates, and (ii) for cyanosilylation, with trimethylcyanosilane (TMSCN) as the cyanosilylating agent and benzaldehyde as the substrate. The mechanistic understanding thus gained has then been further exploited experimentally to bring hydroboration and cyanosilylation closer to experimental conditions in catalysis. These insights can potentially be expanded to the rapidly growing area of solvent-free and internal catalyst chemistry.

Synthesis of four diastereomers of notoryne and their C-13 NMR chemical shifts analysis - Senapati, Sibadatta; Das, Shyamsundar; Dixit, Ruchi; Vanka, Kumar; Ramana, V, Chepuri (Journal of Chemical Sciences, 2021)
In this manuscript we document the details of the synthesis of four diastereomers of notoryne. The synthesis of one of the diastereomer having a similar relative stereochemistry of substituents on the both THF rings like notoryne, however, being the relative stereochemistry between the bridging carbon of these two THF units is changed from anti to syn has been executed mainly to learn how the ring carbon chemical shifts vary with this change. Interestingly, the deviations are found mainly for the carbons of THF ring that bears the Br-group. In addition to this isomer, three more diastereomers having the relative stereochemistry of substituents on either of the THF rings varied have been also synthesized. All four diastereomers have been subjected for extensive NMR studies and their C-13 NMR chemical shifts have been compared with notoryne and laurendecumenyne B. In addition, chemical shifts for the four diastereomers along with these natural products were calculated with the help of DFT calculations and compared to the experimentally obtained chemical shift values.

Silver dependent enantiodivergent gold(i) catalysed asymmetric intramolecular hydroamination of alkenes: a theoretical study - Dixit, Ruchi; Sharma, Himanshu; Agbossou-Niedercorn, Francine; Vanka, Kumar; Michon, Christophe (Catalysts, 2022)
We report a theoretical study of the first silver-dependent enantiodivergent gold-catalysed reaction. The combination of a single chiral binuclear gold(I) chloride complex and silver perchlorate catalyses the asymmetric intramolecular hydroamination of alkenes and affords both enantiomers of the products by applying a simple solvent change from toluene to methanol. A gold-silver chloride adduct that occurs only in methanol appears to control the enantioinversion. If one gold atom coordinates and activates the alkene moiety, the other gold is included in an adduct with silver chloride, which coordinates a methanol solvent molecule and further interacts with the amine function. If the use of toluene implies free anions and affords (S)-enantiomer, methanol allows a proximal interaction with the amine, leads to an opposite stereodifferentiation of the two diastereomeric intermediates during the final protodeauration step and results in the (R)-enantiomer.
Keywords: alkene; enantiodivergent catalysis; Gold; hydroamination; Silver